Relationship of the bone phenotype of the Klotho mutant mouse model of accelerated aging to changes in skeletal architecture that occur with chronological aging - Verlinden, Lieve; Li, Shanshan; Veldurthy, Vaishali; Carmeliet, Geert; Christakos, Sylvia (Frontiers in Endocrinology, 2024)
Introduction: Due to the relatively long life span of rodent models, in order to expediate the identification of novel therapeutics of age related diseases, mouse models of accelerated aging have been developed. In this study we examined skeletal changes in the male and female Klotho mutant (kl/kl) mice and in male and female chronically aged mice to determine whether the accelerated aging bone phenotype of the kl/kl mouse reflects changes in skeletal architecture that occur with chronological aging.Methods: 2, 6 and 20-23 month old C57BL/6 mice were obtained from the National Institute of Aging aged rodent colony and wildtype (+/+) and kl/kl mice were generated as previously described by M. Kuro-o.. Microcomputed tomography analysis was performed ex vivo to examine trabecular and cortical parameters from the proximal metaphyseal and mid-diaphyseal areas, respectively. Serum calcium and phosphate were analyzed using a colorimetric assay. The expression of duodenal Trpv6, which codes for TRPV6, a vitamin D regulated epithelial calcium channel whose expression reflects intestinal calcium absorptive efficiency, was analyzed by quantitative real-time PCR.Results and Discussion: Trabecular bone volume (BV/TV) and trabecular number decreased continuously with age in males and females. In contrast to aging mice, an increase in trabecular bone volume and trabecular number was observed in both male and female kl/kl mice. Cortical thickness decreased with advancing age and also decreased in male and female kl/kl mice. Serum calcium and phosphate levels were significantly increased in kl/kl mice but did not change with age. Aging resulted in a decline in Trpv6 expression. In the kl/kl mice duodenal Trpv6 was significantly increased. Our findings reflect differences in bone architecture as well as differences in calcium and phosphate homeostasis and expression of Trpv6 between the kl/kl mouse model of accelerated aging and chronological aging. Although the Klotho deficient mouse has provided a new understanding of the regulation of mineral homeostasis and bone metabolism, our findings suggest that changes in bone architecture in the kl/kl mouse reflect in part systemic disturbances that differ from pathophysiological changes that occur with age including dysregulation of calcium homeostasis that contributes to age related bone loss.